Vaccination among Medicare-fee-for service beneficiaries: Characteristics and predictors of vaccine receipt, 2014–2017. Issue 9 (21st February 2019) - Shen, Angela K.; Warnock, Rob; Selna, Weston; MaCurdy, Thomas E.; Chu, Steve; Kelman, Jeffrey A.
Abstract: Background: Vaccination coverage rates for older adults are low. To better understand utilization of Medicare vaccination benefits we examined a retrospective cohort of more than 26 million Medicare fee-for-service beneficiaries age 65 years and older from 2014 to 2017. Methods: Multivariate logistic regression was used to obtain marginal effects (ME) describing the association between patient-level characteristics and the likelihood of vaccination. Vaccines routinely recommended by the Advisory Committee on Immunization Practices—seasonal influenza, 23-valent pneumococcal polysaccharide, 13-valent pneumococcal conjugate, and herpes zoster vaccines—were examined. Variables considered include demographics (e.g., age, sex, race), use of preventive services, frailty indicators, and co-morbidities. Results: The mean beneficiary age (SD) for each vaccine examined—seasonal influenza (2016–2017), pneumococcal, and herpes zoster—was 75.0 (7.9) years, 74.5 (7.5) years, 74.5 (7.4) years respectively; and 43.7%, 43.2%, and 39.5% were males respectively. Adjusted marginal effects showed that Black beneficiaries were less likely to receive any of the three vaccines compared to White beneficiaries, while North American Native beneficiaries were most likely to receive a pneumococcal vaccine. Trends by race and sex were similar across all ages. Beneficiaries utilizing preventive services, particularly cardiovascular disease screening (ME of 13.8%, 15.6% and 1.5% for influenza, pneumococcal and herpes zoster vaccine respectively), other vaccinations, and the Medicare Annual Wellness Visit (ME of 9.8%, 15.3% and 0.4% respectively) were predictors of vaccination for all three vaccines. For herpes zoster vaccines, beneficiaries in rural settings (ME of 1.0%) and those who are dual-eligible for Medicare and Medicaid insurance (ME of 1.7%) were more likely to receive herpes zoster vaccine than beneficiaries in urban settings and those not dual-eligible, respectively. Conclusion: Medicare beneficiaries of certain demographic with selected comorbid conditions are less likely to receive routinely-recommended vaccines. Strategies and interventions can target such sub-populations of Medicare beneficiaries by optimizing the utilization of preventive services.